Assessing inequalities in sustainable access to improved water services using service level indicators in a rural municipality of South Africa - Calvin Sambo (IWA Publishing, 2021)
Sustainable access to improved water services is a human right recognized by the Sustainable Development Goals (SDG) agenda and the constitution of South Africa. In recognition of this, South Africa implemented the Free Basic Water (FBW) policy outlining six recommended service level standards (e.g. distance, reliability and cost) to guide improved water services provision, especially in rural municipalities. However, despite implementing the rights-based approach policy, a significant proportion of the rural population is reported to have limited/poor access to improved water services. For this reason, the study adopted the FBW standards as indicators to assess inequalities in sustainable access to improved water services in Makhudutamaga Local Municipality (MLM) in South Africa. The findings indicate inequalities in access to improved water services based on FBW standards. Overall, the improved water services complied with the FBW standard for distance but not with the other standards. The non-compliance with the other standards indicated limited/poor access to improved water services and improper implementation of the FBW policy. This work provides water managers with an understanding of levels of water services provided based on FBW standards for planning and management to improve access to improved water services and enforce proper implementation of the FBW policy. HIGHLIGHTS Aspects of the improved water services did not comply with standards of Free Basic Water (FBW) policy.; Free Basic Water (FBW) policy was not properly implemented.; There were inequalities in access to improved water services.; Unreliability of water services is a challenge affecting sustainable access to improved water services.;